ISOLASI DAN UJI POTENSI BAKTERI NITRIFIKASI ASAL TANAH KEBUN KELAPA SAWIT DENGAN APLIKASI TANDAN KOSONG DAN LIMBAH CAIR PABRIK KELAPA SAWIT - Huryatul Islam; Nelvia Nelvia; Delita Zul (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2021)
This study aimed was to isolate nitrifiying bacteria from oil palm plantations fertilized with empty fruit bunch (EFB) and palm oil mill effluent (POME) and to analyze their potency. The soil samples were sampled from private oil palm plantations by purposive sampling method are mixed application (EFB + POME), EFB application, POME application and without application (C), and each location was taken 3 times. Isolation of nitrifiying bacteria was perfomed by using Nitrosomonas sp. and Nitrobacter sp. spesific media. The parameters observed were bacterial cells number, number of isolates and their potency. The results showed cells number of nitrifiying bacteria range 8.0 – 11.40 x 105cfu g-1 soil. A total of 18 isolates were isolated and potentially oxidized ammonium and nitrate. The best potential of bacteria in oxidizing ammonium at a concentration of 500 ppm (NH4)2SO4 was isolate NSC34 (3.4 ppm), and isolate with the best potential to produce nitrate at a concentration of 500 ppm (NH4)2SO4 were isolate of NBC225 (26.1 ppm). The most optimal activity of isolate bacteria to nitrifiying occurred at a concentration of 500 ppm (NH4)2SO4 and at 4 days incubation time.Key words : Nitrifiying bacteria, palm oil empty fruit bunch, palm oil mill effluent